Cloning of a small, acid-soluble spore protein gene from Bacillus subtilis and determination of its complete nucleotide sequence. - Connors, M J (1985)
The first Bacillus subtilis small, acid-soluble spore protein (SASP) gene has been cloned by using previously cloned B. megaterium SASP genes as DNA-DNA hybridization probes. Determination of the DNA sequence of the B. subtilis SASP gene showed that it codes for a 72-residue protein (termed SASP-1) containing a single spore protease cleavage site as well as other sequences conserved in Bacillus megaterium SASPs A, C, C-1, C-2, and C-3. The B. subtilis SASP-1 genes's coding sequence is preceded by a potential Bacillus ribosome-binding site, and is followed by a sequence that could form a stem-and-loop structure characteristic of transcription termination sites. Upstream from the coding sequence there are no obvious homologies with other B. subtilis sporulation genes, but similarities with B. megaterium SASP genes are evident. SASP-1 mRNA (290 bases long) is absent from vegetative cells, but appears midway in sporulation and then disappears. The cloned SASP-1 gene hybridizes to three bands other than the SASP-1 gene itself in EcoRI or HindIII digests of B. subtilis DNA. Presumably these other bands represent SASP genes related to the SASP-1 gene, and we have been able to detect at least three such proteins in B. subtilis spores.